The relationship between serum ghrelin levels and bone metabolism markers and severity anemia in non-diabetic hemodialysis patients; a pilot study - Leila Mahmoodnia; Sara Beigrezaei; Mohammad Reza Tamadon; Tina Jafari; Marzieh Kafeshani; Fatemeh Mahmoodi; Ali Hasanpour Dehkordi; Masoud Amiri (Society of Diabetic Nephropathy Prevention, 2018)
Background: Chronic kidney disease (CKD) is a consequence of progressive and irreversible destruction of nephrons, mainly due to uncontrolled diabetes mellitus and high blood pressure. Ghrelin is a peptide hormone which could play a substantial role in hunger sensation, may increase body fat percentage and might adjust the long-term body weight and is mostly secreted in the stomach. Objectives: This study aimed to evaluate the relationship between ghrelin levels and various biochemical and demographic indices in a group of non-diabetic hemodialysis patients. Patients and Methods: Around 39 non-diabetic patients undergoing hemodialysis in Hajar hospital at Shahrekord city were enrolled. Results: The mean age of patients was 57.10±20.20 years. Their mean weight was 56.65 ±16.25 kg. Their hemoglobin level mean was 10.43±1.84 g/dL. The serum ghrelin level had a positive but not significant correlation with the age, dialysis quality, dosage, calcium level, alkaline phosphatase (ALP), parathormone, vitamin D and hemoglobin in these patients. Conclusions: More studies in this subject of hemodialysis patients to define the exact role of ghrelin in hemodialysis patients are recommended.